2002
DOI: 10.1002/jcb.10382
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical role of apoptosis in tumor progression

Abstract: Tumors frequently acquire resistance to apoptosis that is expected to contribute to malignant phenotype and reduce sensitivity to treatment. In fact, inactivation of p53 tumor suppressor gene resulting in suppression of apoptosis serves as a negative prognostic marker. Surprisingly, expression of a strong anti-apoptotic protein Bcl-2, another mechanism to avoid apoptosis, was found to be associated with a favorable prognosis. This paradoxical anti-progressor function of Bcl-2 has been explained in literature b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 34 publications
2
19
0
3
Order By: Relevance
“…The prime determinant of the dormant state proves not to be a limited immortal (stem cell) composition per se, but to a limited ability of stem cells to migrate, coupled, curiously, with a limited death rate and excess replicative potential among the nonstem cells. This finding corroborates recent observations of an inverse dependence between these factors and malignant progression (8,9).…”
Section: Introductionsupporting
confidence: 93%
“…The prime determinant of the dormant state proves not to be a limited immortal (stem cell) composition per se, but to a limited ability of stem cells to migrate, coupled, curiously, with a limited death rate and excess replicative potential among the nonstem cells. This finding corroborates recent observations of an inverse dependence between these factors and malignant progression (8,9).…”
Section: Introductionsupporting
confidence: 93%
“…For example, in a murine model of c-mycinduced B cell lymphoma, Bcl-2 expression abrogated the selective pressure(s) needed to lose p53 and prevented the formation of aneuploid cells [8]. Similar observations with regard to Bcl-2 were also observed in other models [9]. In contrast, increased Bax (Lck-Bax38/1) was associated with accelerated tumor formation in both p53 +/+ and p53 −/− mice [4,10].…”
Section: Introductionmentioning
confidence: 65%
“…It has also been suggested that adenomatous growth and tumor invasion are two different phases of tumor progression, and it may be during the later phase of tumor invasion, when the apoptotic stresses are different, that selection of a different means of inhibition of apoptosis (such as p53 dependency) occurs [31,32,41]. Furthermore, Gurova and Gudkov [42] recently reviewed studies related to the paradoxical role of apoptosis in tumor progression and concluded that inhibition of apoptosis does not lead to loss of genomic stability but rather creates a tumor environment that no longer supports further tumor progression. Therefore, inhibitors of apoptosis can be considered as factors suppressing tumor progression.…”
Section: Discussionmentioning
confidence: 99%